Autologous blood coagulum is a physiological carrier for BMP6 to induce new bone formation and promote posterolateral lumbar spine fusion in rabbits. (10th November 2019) - Vukicevic, Slobodan; Grgurevic, Lovorka; Erjavec, Igor; Pecin, Marko; Bordukalo‐Niksic, Tatjana; Stokovic, Nikola; Lipar, Marija; Capak, Hrvoje; Maticic, Drazen; Windhager, Reinhard; Sampath, T. Kuber; Gupta, Munish
Abstract: In the present study, we describe autologous blood coagulum (ABC) as a physiological carrier for BMP6 to induce new bone formation. Recombinant human BMP6 (rhBMP6), dispersed within ABC and formed as an autologous bone graft substitute (ABGS), was evaluated either with or without allograft bone particles (ALLO) in rat subcutaneous implants and in a posterolateral lumbar fusion (PLF) model in rabbits. ABGS induced endochondral bone differentiation in rat subcutaneous implants. Coating ALLO by ABC significantly decreased the formation of multinucleated foreign body giant cells (FBGCs) in implants, as compared with ALLO alone. However, addition of rhBMP6 to ABC/ALLO induced a robust endochondral bone formation with little or no FBGCs in the implant. In rabbit PLF model, ABGS induced new bone formation uniformly within the implant resulting in a complete fusion when placed between two lumbar transverse processes in the posterolateral gutter with an optimum dose of 100‐μg rhBMP6 per ml of ABC. ABGS containing ALLO also resulted in a fusion where the ALLO was replaced by the newly formed bone via creeping substitution. Our findings demonstrate for the first time that rhBMP6, with ABC as a carrier, induced a robust bone formation with a complete spinal fusion in a rabbit PLF model. RhBMP6 was effective at low doses with ABC serving as a physiological substratum providing a permissive environment by protecting against foreign body reaction elicited by ALLO.